Influence of laser pulse regime on the structure and optical properties of TiO2 nanolayers. (28th September 2018) - Peñaloza-Mendoza, Y; Alvira, F C; Caballero-Briones, F; Guarneros-Aguilar, C; Ponce, L
Abstract: TiO2 films were deposited onto glass substrates by pulsed laser deposition (PLD) in high vacuum under monopulse and multipulse excitation. After deposition, a thermal treatment on air atmosphere was done to promote crystallization. Films were studied by x-ray diffraction, energy dispersive spectroscopy, scanning electron, atomic force microscopy, UV–vis spectroscopy, and ellipsometry. After air annealing, films gain a different amount of oxygen: TiO1.9 in multipulse regime versus TiO1.7 in the monopulse one. Splashing is observed in both regimes although in the multipulse mode greater particles are found, that derived in a less compact film after annealing which could be the cause of the better oxygen diffusion. The optical band gap of the film prepared with monopulse excitation is 3.09 eV. This value increased to 3.34 eV with annealing, corresponding to that of anatase. The film made with multipulses has an Eg = 3.12 eV which was invariant upon annealing. The difference in the properties of the films grown in the different regimes was attributed to the re-excitation of the plasma during the ablation process in the multipulse ablation that leads to an increased splashing density and thereafter a less compact film and the presence of off-stoichiometry inclusions within the film bulk.